The language of risk : Self-assessment of nasopharyngeal cancer risk - Edmund Ui Hang, Sim; Ting, Su Hie (2022)
The language of risk is a part of medical discourse that lay people have problems understanding. Scientists, doctors and patients speak a different language of risk because they understand risk differently. Scientists talk about risk factors and the likelihood of the disease while patients experience risk at a personal level (Gifford 1986). Scientists estimate level of risk in numbers but doctors and patients translate risk information to the groups that are more likely to be at risk and what signs appear before the onset of illness (Gifford 1986). For doctors and patients, the distinction between risk and cause is blurred (Jasen 2002). Lupton (1995) categorises risk factors as external factors which are beyond one’s control (e.g., family history), and internal factors which are within one’s control (e.g., dietary habits). Patients often have their own understanding of why cancer might develop and why they delay seeking of treatment, which may not align with scientific knowledge (Jasen 2002). Much of the research on the language of risk in relation to diseases have focused on breast cancer (e.g., Jasen 2002; Lobb et al. 1999). Women also have problems understanding prognostic information delivered by doctors (Lobb et al. 1999). Traditionally it was clinical examinations that confirmed whether one had a disease, but nowadays self-examination is encouraged for early detection. There is a lack of findings on understanding of risk information for nasopharyngeal (nose and throat) cancer which is not common in Western settings. However, nasopharyngeal cancer incidence is high in Asian countries, particularly in China, Indonesia, Vietnam, India and Philippines (Kumar et al. 2019). In Malaysia, nasopharyngeal cancer incidence is number five, affecting 4% of the population, based on the National Cancer Registry 2012-2016 (Ministry of Health Malaysia 2019). The incidence is high among males (age-standardised incidence rate of 5.2, ranked fifth among cancers) but not among the top 10 cancers for females. The 25-59 years old group (11.3%) is the most susceptible. This cancer is more common among the Chinese males, compared to Malay and Indian males (age-standardised incidence rates of 8.6, 2.7 and 0.6 respectively). Nasopharyngeal cancer incidence is also particularly high among the Bidayuh indigenous group of Sarawak (Devi et al. 2004; Kumar et al. 2019). Hence, studies on self-assessment of risk factors and potential signs of the cancer are needed. The preliminary study on nose and throat cancer risk involved 101 respondents (55.4% male, 44.6% female). The age distribution is as follows: below 20 (6.9%), 20-39 (61.4%), 40-59 (21.8%), 60 and above (9.9%). There were more Malays (31.7%) and Chinese (38.5%) among the respondents, followed by Others (12.9%), Iban (6.9%), Bidayuh (5.0%), Indian (3%), Orang Ulu (1%) and Kadazandusun (1%). The instrument was a questionnaire on external risk factors (family history, 1 item) and internal risk factors (lifestyle, 3 items), and signs (4 items). Demographic information obtained were gender, age and ethnic background which are linked to nasopharyngeal cancer incidence in Malaysia. Respondents filled in the questionnaire after they had given consent. Subsequently, the data on risk factors and signs were computed to obtain a nasopharyngeal cancer assessment score. The risk associated with gender, age, ethnic group and signs were weighted for the computation. At the research exposition, the respondents could see the score and the risk level: low, moderate, high. They were also given an interpretation of what the risk score meant in terms of health protective measures. The results showed an average nasopharyngeal cancer risk score of 10.7 points out of the maximum of 48 points (range: 3-20). When converted to 100%, the average is 22.3% (range: 6.2%-41.7%). This means that on average, the respondents were at low risk of having nasopharyngeal cancer. Pearson correlation tests showed that there was no relationship between the nasopharyngeal cancer risk score and age. The t-test showed that there were also no significant differences between male and female respondents in their cancer risk score. As for ethnic group, the mean scores show some variation: Chinese (24.6%), Bidayuh (24.2%), Malay (22.7%), Iban (22.3%), Others (16.9%), and Indian (13.1%). The Orang Ulu and Kadazandusun were grouped with ‘Others’ category as there was only one respondent each. Among the lifestyle risk factors, the greatest risk is from consumption of preserved food, followed by exposure to chemicals and smoking. Smoking was a minimal risk factor for the respondents. A small percentage (0.8%) were non-smokers, 95% reported that they rarely smoked and 1% smoked one to three cigarettes per month and 4% smoked more than five cigarettes per day. The respondents were at minimal risk to nasopharyngeal cancer due to exposure to hazardous chemicals (no exposure, 86.1%; exposure, 13.9%). However, this group was at greater risk due to their consumption of preserved food (never, 2%; one to two times per year, 20.8%; one to two times per month, 54.5%; once per week, 22.8%). Nasopharyngeal cancer risk from family history was generally low for the respondents. The results showed that 91.1% did not have a family history of the cancer, while 6.9% had one uncle or aunt, and 2% had one parent who contracted the cancer. The results on the four early signs of nasopharyngeal cancer are as follows, arranged in the order of progressively more certain signs of the cancer: (1) Symptoms of common cold or flu, such as sore throat, cough, and running nose: less than 2 times per year, 43.6%; 3-5 times per year, 39.6%, 3 times per month, 16.8%; (2) Ear pain: nul incidence, 78.2%; occasional incidence, 19.8%; frequent incidence, 2%. (3) Blood in sputum or nasal discharge: nul incidence, 82.2%; occasional incidence, 16.8%; whenever they coughed, 1%. (4) Lump in neck area: absence, 98%; presence, 2%. The small percentage who reported blood in their sputum or nasal discharge and a lump in the neck area may be at risk of nasopharyngeal cancer. Taken together, about one-quarter of the respondents self-reported presence of lifestyle risk factors, family history and nasopharyngeal cancer signs (25% Indian respondents, 20.7% Malay respondents, 23.7% Chinese respondents). In conclusion, our results showed that respondents could perform self-assessment of cancer risk if the ‘diagnostic questions’ were phrased in everyday language and about tangible matters. In our study, we showed the nasopharyngeal cancer risk score in numerical form to respondents because this kind of information appears scientific. However, to help them understand the language of risk, we worded the ‘diagnostic outcome’ as low, moderate and high risk. For example, the high-risk respondents were told, ‘NasoCRA indicates a moderate to high NPC risk. We strongly suggest that you seek medical assistance from relevant medical specialist(s) as soon as possible to get further professional advice, and proper diagnosis. It is necessary that you consider quarterly to half yearly medical check-up’. The findings suggest that to help the lay person understand the language of risk, it is important to provide the risk information in both numerical and text form, and to focus the information on health measures within their control.